2017
DOI: 10.3928/23258160-20170301-06
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Effects of Early Switching to Ranibizumab or Aflibercept in Diabetic Macular Edema Cases With Non-Response to Bevacizumab

Abstract: Aflibercept and ranibizumab both appear to be effective for patients showing no initial response to bevacizumab. [Ophthalmic Surg Lasers Imaging Retina. 2017;48:230-236.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
2
17
0
Order By: Relevance
“…Following the same pattern, more eyes had an increase of more than 15 letters in the ranibizumab group compared with the aflibercept group. Similar outcomes have been already described by Ashraf et al 13 who reported that despite a significant CFT decrease after the switch to ranibizumab or aflibercept in eyes with DME refractory to bevacizumab, a significant improvement in BCVA was observed only with ranibizumab but not with aflibercept. As it is already well established, there is an association between DRIL, increasing severity of diabetic retinopathy, and a poor VA outcome with treatment.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Following the same pattern, more eyes had an increase of more than 15 letters in the ranibizumab group compared with the aflibercept group. Similar outcomes have been already described by Ashraf et al 13 who reported that despite a significant CFT decrease after the switch to ranibizumab or aflibercept in eyes with DME refractory to bevacizumab, a significant improvement in BCVA was observed only with ranibizumab but not with aflibercept. As it is already well established, there is an association between DRIL, increasing severity of diabetic retinopathy, and a poor VA outcome with treatment.…”
Section: Discussionsupporting
confidence: 89%
“…[10][11][12] Much less evidence exists on the real efficacy differences between aflibercept versus ranibizumab treatment after an initial bevacizumab regimen. 13 Retinal edema is responsible for retinal microstructural changes, retinal atrophy of photoreceptors and ganglion cell lesions. 14 It may also be considered consensual that the best improvements in visual acuity are achieved when retinal edema is resolved.…”
Section: Introductionmentioning
confidence: 99%
“…Ashraf et al [339] performed a retrospective study of 59 eyes from 45 patients with DMO that were treated with bevacizumab, and were, per the Protocol T definition, classed as non-responders, and were switched to aflibercept or ranibizumab. BCVA significantly improved in eyes switched to ranibizumab, and significant decreases in CST were observed in both the ranibizumab and aflibercepttreated eyes.…”
Section: Evidence Reviewmentioning
confidence: 99%
“…Several studies have evaluated the effects of switching anti-VEGF agents on DME outcomes. [16][17][18][19][20][21][22] Prior studies showed that anatomic outcomes improved after switching, but they varied in their conclusions regarding VA, 18 with some reporting no improvements in VA 22 and others finding significant improvement. [16][17][18][19][20][21] Our study demonstrated a statistically significant decrease in CST, but the BCVA improvement was not significant at 12 months across the entire cohort.…”
Section: Discussionmentioning
confidence: 99%